Hankel Determinants of Zeta Values - Haynes, A.; Zudilin, W. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
We study the asymptotics of Hankel determinants constructed using the values ζ(an+b) of the Riemann zeta function at positive integers in an arithmetic progression. Our principal result is a Diophantine application of the asymptotics.